Development of Interactive Learning Videos for Slow Learner Students in Inclusive Higher Education - Rafikayati, Ana; Badiah, Lutfi Isni (Jurnal Pendidikan Kebutuhan Khusus, 2026)
This study aims to develop interactive learning videos for slow learner students in inclusive higher education. The study was conducted at Universitas PGRI Adi Buana Surabaya, involving two slow learner students enrolled in the ENT Anatomy and Audiology course as research participants. This study employed a research and development method with four stages: needs analysis, product design, product development, and limited trials. Data were collected using questionnaires, and data analysis was conducted through quantitative analysis using mean score calculations from evaluations by content experts, media/design experts, and student participants. The research output was an interactive learning video were developed in H5P format and integrated into the VIRLENDA Learning Management System of Universitas PGRI Adi Buana Surabaya. The feasibility test results indicated that the video obtained a score of 3.7 from content experts 3.6 from media experts and 3.7 from users (research participants). Product feasibility was determined based on expert validation scores, with a mean score range of 3.26–4.00 indicating that the interactive learning video was categorized as highly feasible. Based on these feasibility results, it can be concluded that the interactive learning video developed in this study is suitable for limited trials and requires further large-scale effectiveness testing.